배열 안테나의 상관성 신호에서 원하는 신호 추정 방법에 대한 연구 - 이민수(Lee, Min-Soo) (한국정보전자통신기술학회 논문지, 2015)
In this paper, we studied for modified MUSIC algorithm of direction of arrival (DOA)estimation. Modified MUSIC algorithm search optimal covariance matrix using singular value decomposition and Bayes method, and desired signals are estimated by updating weight. In order to estimation of desired signals, we used sub spatial method of MUSIC algorithm. General MUSIC algorithm can estimate a desired signal in case of non-correlation signal. But, general MUSIC algorithm in case of correlation signal can not estimate a desired signals and resolution is decreased. Though simulation in case of correlation signal, we analyze to compare proposed MUSIC algorithm with general MUSIC algorithm. 본 논문에서는 수정된 MUSIC 도래 방향 추정 알고리즘에 대해서 연구 하였다. 수정된 MUSIC 알고리즘은 특이 값 행렬과 베이즈 방법을 적용시켜 공 분산행렬을 최적화 시키고 가중치를 갱신하여 원하는 신호를 추정하는 방법이다. 그리고 MUSCI 알고리즘의 신호 부 공간 방법을 적용시켜 원하는 신호를 정확히 추정하였다. 무상관 신호가 수신 시스템에 입사하면 기존의 MUSIC알고리즘으로 원하는 신호를 추정 할 수 있다. 그러나 일반적으로 수신 시스템에는 상관성 신호가 입사하므로 기존의 MUSIC알고리즘으로 원하는 도래 방향 신호를 추정할 수 있는 능력이 현저히 떨어진다. 모의실험을 통해서 상관성 신호인 경우에 본 연구에서 제안된 MUSIC알고리즘과 기존의 MUSIC알고리즘의 성능을 비교 분석한다.